Evaluation of motor deficits and perihaematomal neuronal degeneration in a mouse model of cerebellar haemorrhage - Salihu, Abubakar Tijjani (2016)
Improved clinical imaging and early surgery, when indicated, have been shown to decrease mortality rate after cerebellar haemorrhage. Nonetheless, the long term functional outcome in the majority of the survivors is still very alarming; irrespective of whether they receive surgical or conservative management. Evidently, the development of definitive medical treatment to use alone or in combination with surgery in order to improve outcome in this condition is hampered by lack of proper understanding of the disease pathophysiology. Following cerebellar haemorrhage, brain tissue inside the hematoma can be considered equivalent to the ischemic core in ischaemic stroke, and is unlikely to be salvageable. However, delayed neuronal loss due to various secondary injury mechanisms might continue in the vicinity of the haemorrhage and this could contribute to the persistent disability in the patients. The aim of this study is to evaluate the histomorphological changes of the perihaemorrhagic tissue after experimental cerebellar haemorrhagen in mice. We hypothesized that delayed neuronal degeneration occurs in the perihaematomal area after intracerebellar haemorrhage. Adult male Swiss albino mice were stereotactically infused with collagenase type VII (0.4U in 1ml saline) unilaterally in to the cerebellum, following anaesthesia. The animals in the sham group were injected with normal saline, while the control animals were not injected with anything. Motor deficits were assessed using open field and composite score for evaluating mouse model of cerebellar ataxia at 1, 3, 7, 14 and 21 days after collagenase infusion and the animals were sacrificed at the same time interval for evaluation of perihaematomal neuronal degeneration using haematoxylin and eosin staining and Annexin V-FITC/ Propidium iodide assay. At the end of the study, it was found that infusion of 0.4U collagenase produces significant locomotor and ataxic deficit in the mice especially within the first week post surgery and this gradually improved within three weeks. Neuronal degeneration evident by cytoplasmic shrinkage and nuclear pyknosis was observed at the perihaematomal area after one day; especially at 3 and 7 days post haemorrhage. By 21 days, both the haematoma and degenerating neurons in the perihaematomal area were phagocytosed and the remaining neuronal cells around the scar tissue appear normal. Moreover, Annexin-V/propidium iodide–positive cells were observed at the perihaematomal area at 3 and 7 days implying that the neurons likely die via apoptosis. It was concluded that a population of potentially salvageable neurons exist in the perihaematomal area after cerebellar haemorrhage throughout a wide time window that could be amenable to treatment.